2007
DOI: 10.1007/s00415-006-0402-x
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus at relapses of multiple sclerosis

Abstract: The possible participation of different herpes viruses was studied during exacerbations of multiple sclerosis (MS). We searched for the presence of DNA from the following herpes viruses: varicella zoster virus (VZV), herpes-simplex viruses 1 and 2; Epstein-Barr virus (EBV) and human herpes-virus-6 (HHV6) in mononuclear cells from patients with MS during relapse (n = 40), MS during remission (n = 131) and controls (n = 125). Additionally, immune cells containing viral antigens were quantified by flow cytometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 46 publications
7
45
0
Order By: Relevance
“…When the presence of the virus DNA in total blood, cells, plasma, CSF or brain biopsy was analysed, only one of the studies found a relationship between the infection and the disease [40]. On the other hand, it is known that EBV DNA in serum is present in most patients in the acute phase of MS, as a consequence of the virus replication; however, during the latency stage, its detection in plasma or CSF is more difficult, although the higher viral load will be found in B lymphocytes [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the presence of the virus DNA in total blood, cells, plasma, CSF or brain biopsy was analysed, only one of the studies found a relationship between the infection and the disease [40]. On the other hand, it is known that EBV DNA in serum is present in most patients in the acute phase of MS, as a consequence of the virus replication; however, during the latency stage, its detection in plasma or CSF is more difficult, although the higher viral load will be found in B lymphocytes [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sanders et al [39] found a small proportion of positive cases in the brain tissue, with no differences between patients with active and inactive demyelinating plaques. Neither were there any differences when remittent or recurrent patients were considered [27,40]. However, lytic and latent infection markers have recently been found in the CSF of MS patients, in ectopic follicles [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier studies that evaluated whole CSF IgG from MS patients identified antibodies to several different viruses, such as measles, varicella zoster, human T-lymphocytic virus 1, and human hepatitis virus 6 (7), whereas other investigations found antibodies targeting major myelin proteins, myelin basic protein (MBP) and myelin oligodencrocyte glycoprotein (MOG) (8,9) as well as glycolipids, fatty acids, and neurofilament proteins (10). Similarly, more recent investigations that have applied single-cell PCR cloning to individual CSF B cells in MS have detected antibodies to certain viruses or myelin proteins (11)(12)(13). However, it has been impossible to match specificity of antibodies identified in CSF to OCB by studying whole CSF IgG or recombinant antibodies constructed from rearranged Ig heavy-and light-chain genes in individual B cells.…”
mentioning
confidence: 99%
“…Reports on the presence of HHV-6 DNA in peripheral blood mononuclear cells (PBMCs) or peripheral blood from healthy controls vary considerably. Sotelo et al [36] and Hon et al [37] reported HHV-6 DNA absent, Fredj et al [38] in 2.0%, Hay and Tenser, [35] in 14%, and Mameli et al [39] in 21.4% of healthy controls. lvarez-Lafuente et al [31], Alvarez-Lafuenteet al [40], and Chapenko et al [30] reported higher prevalence rates, 30.4%, 21.6%, and 28.7% respectively, while Ablashi et al [41] reported HHV-6 DNA in PBMCs from 60.0% of healthy controls.…”
Section: Authorsmentioning
confidence: 97%